Planning Ahead: Advanced Prediction of Car User’s Intention to Use the Future Railway system in Libya (Journal of Pure & Applied Sciences, 2021)
This study was conducted to examine the car users’ willingness to take new railway system for intercity travel in Libya to reduce car accident on intercity highways. This study introduced three novel constructs; namely novelty seeking (NS), trust (TR), and external influence (EI) (mass media campaign) into the theory of planned behaviour (TPB). A total of   338 respondents from five major cities in Libya (Benghazi, Tripoli, Misrath, Tobruk and Surt) were participates in this study. The findings revealed that the attitude (AT: 0.236***) toward new railway system, subjective norms (SN: 0.062), and perceived behaviour control (PBC: 0.149**) is directly and positively affect the behaviour intention of car users in Libya to take new railway system for intercity travel. Furthermore, the novelty seeking (NS: 0.131*) shows indirect and positive relationship between behaviour intentions via attitude. Trust (and external influence were found to have a positive effect towards three behaviour intention to take railway system’s antecedents (T-AT: 0.551***, T-SN: 0.387*** and T-PBC: 0.376***). However, not limited to these three antecedents, external influence also reported the direct and positive influence on the trust and novelty seeking. Ultimately, the theoretical and marketing implications of the transportation arena were derived. This study was considered as a hint to new railway system authorities in Libya to arrange the strategy to attract the car users to choose new railway system as travel alternative for intercity travel.